The 'normobaric oxygen paradox': does it increase haemoglobin? - De Bels, David; Theunissen, Sigrid; Devriendt, Jacques; Germonpré, Peter; Lafere, Pierre; Valsamis, Joseph; Snoeck, Thyl; Meeus, Philippe; Balestra, Costantino (Diving and hyperbaric medicine, 2012)
A novel approach to increasing erythropoietin (EPO) using oxygen (O2) (the 'normobaric oxygen paradox') has been reported in healthy volunteers. We investigated whether the EPO increase is sufficient to induce erythropoiesis by comparing two protocols of O2 administration. We compared the effect of daily versus alternate days 100% O2, breathed for 30 minutes, on haemoglobin concentrations during a 12-day period. Nine subjects underwent the two protocols six weeks apart. We observed a significant increase in haemoglobin (as a percentage of baseline) in the alternate-days group compared to the daily group and to baseline after four days (105.5 ∓ 5.7 % vs. 99.6 ∓ 3.3 % difference from baseline; P < 0.01). At the end of the experimental period, haemoglobin values increased significantly compared to baseline in both groups. There was a significant percentage rise in reticulocyte count in the alternate-days group compared to the daily group (182 ∓ 94 % vs. 93 ∓ 34 %; P < 0.001). The normobaric oxygen paradox seems effective in increasing haemoglobin in non-anaemic, healthy volunteers, providing sufficient time is allowed between O2 applications. The exact time interval is not clearly defined by this study but should probably be at least or greater than two days. Further studies are needed to define more precisely clinical applications in the use of O2 as a pharmaceutical agent.